PENYELESAIAN SENGKETA PENCEMARAN LINGKUNGAN LAUT DALAM KASUS TUMPAHAN MINYAK MONTARA DI LAUT TIMOR - Ni Putu Suci Meinarni (University of Udayana, 2016)
Diplomacy as a means of communication made by various parties, including the negotiations between representations who have been recognized or defined as well as the negotiations when it was not possible to see a bright spot, the one party or two countries who consider necessary, can choose the path of another in the settlement of disputes. Regarding the case Montara, Indonesia can choose the legal path is through ITLOS. When all lanes closed negotiations and diplomacy, international legal channels under the umbrella of ITLOS is open for the settlement of cases of oil spills in the Montara platform. If ITLOS considered too early to have as a line dispute resolution, since the country rarely choose ITLOS as a settlement of the dispute, as evidenced since it entry into force (between 1994 to 2006), only 13 cases were handled by ITLOS, and in UNCLOS itself is possible for more flexible judicial selection and Arbitration still in the high demand. Diplomasi sebagai suatu cara komunikasi yang dilakukan oleh berbagai pihak termasuk negosiasi antara wakil-wakil yang sudah diakui atau yang diartikan pula sebagai perundingan-perundingan ketika sudah tidak memungkinkan untuk menemui titik terang maka salah satu pihak maupun kedua negara yang mengganggap perlu, dapat memilih jalur lain dalam penyelesaian sengketa. Berkaitan dengan kasus Montara, Indonesia dapat memilih jalur hukum yaitu melalui ITLOS. Bila semua jalur negosiasi dan diplomasi tertutup, jalur hukum internasional dibawah payung ITLOS terbuka untuk penyelesaian kasus tumpahan minyak di sumur Montara. Apabila ITLOS dianggap terlalu dini untuk dipilih sebagai jalur penyelesaian sengketa, karena memang negara jarang sekali memilih ITLOS sebagai tempat penyelesaian sengketa, terbukti sejak entry into force (diantara tahun 1994 sampai dengan tahun 2006), hanya 13 kasus yang di tangani ITLOS di dalam UNCLOS masih memungkinkan adanya pilihan peradilan yang lebih fleksbel dan lebih diminati oleh negara-negara yaitu Arbitrase.